Elephantine, Ägypten. Neues zu Lebenswirklichkeiten (Projekt »Realities of Life«) im späten Mittleren Reich am ersten Nilkatarakt. Weitere Forschungsergebnisse der Jahre 2019 und 2020 - Sigl, Johanna (e-Forschungsberichte des DAI, 2020)
Within the Middle Kingdom living quarters of the town of Elephantine, the German Archaeological Institute Cairo is focusing in the scope of the project »Realities of Life« on all kinds of finds down to the smallest samples to gain insight into daily life on the island around 1800 BCE. The study of ash deposits and fireplaces in House 169 has recently been especially rewarding. Evidence for food production, waste management and animal keeping during the habitation periods of this building in the northwestern town could be gained. Statistical methods used on the only rarely studied find group of dung underlines the results from the zooarchaeological analysis of animal remains, which suggest that goats were the predominantly kept caprine on the island.